A new Cinygmula McDunnough, 1933 species with distinct imaginal frontal fold from eastern Chinese Himalaya (Ephemeroptera: Heptageniidae) - Ding, Bei-Tian; Gong, De-Wen; Zhou, Chang-Fa (Zootaxa, 2024)
In the family Heptageniidae (Ephemeroptera), Cinygmula hutchinsoni (Traver, 1939) from central Asia is the only species known to possess pointed claws and a distinct frontal fold. Here, a second similar species with the same combination of characters is described. Cinygmula longissima sp. nov. is found in the eastern Himalaya of China, shows stouter imaginal penes, darker wingbases, and narrower nymphal gills than the previous one. This discovery indicates that this species of Heptageniidae are not limited to central Asia but live in high-altitude alpine habitats.